A Code Compression Method to Cope with Security Hardware Overheads - Wanderley, Eduardo; Vaslin, Romain; Gogniat, Guy; Diguet, Jean-Philippe (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2007: Anais do XIX International Symposium on Computer Architecture and High Performance Computing, 2007)
Code Compression has been used to alleviate the memory requirements as well as to improve performance and/or minimize energy consumption. On the other hand, implementing security primitives on Embedded Systems is always costly in terms of area and performance. In this paper we present a code compression method, the IBC-EI (instruction based compression with encryption and integrity checking), tailored to provide integrity checking and encryption to secure processor-memory transactions. The principle is to keep the code compressed and ciphered in the memory, thus reducing the memory footprint and providing more information per memory access. For the Leon processor and a set of benchmarks from the Mediabench and MiBench suites the habitual overheads due to security trend to zero in comparison to a system without security neither compression.